The strengthen of the second pillar in the European Union and Hungary - Nagy, Zsuzsanna (Acta Agraria Debreceniensis, 2006)
The Common Agriculture Policy (CAP) took shape in the early 1960s. At that time the first action was to stop food shortages. Among the objectives of the Treaties of Rome appeared the subvention of rural development had not yet.Rural development appeared, in 1992, in connection with accompanying measures, and by end of decade, the European Agricultural Model had taken shape. Agenda 2000 pointed out the direction of rural development and introduced the first and second pillars in the CAP. The regulations of rural development were simplified by 1257/1999/EC, which stressed the importance of rural development to and it has to continue the principle of subsidiarity and has to be decentralized.The last enlargement raised new problems, the mid-term review of Agenda 2000 occurred and resulted in a new CAP-reform in 2003. The 1783/2003/EC rural development regulation modified the previous regulation. According to the new regulation it is necessary to strengthen the new rural development policy, enlarge the circles of accompanying measures, place greater emphasis on requirements of environment, human resource, animal welfare and plant health. Digression and modulation take part in the new CAP-reform in order to increase the role of rural development in the common budget.In the next budget from 2007-2013, the European Union wants to create a single rural development fund and simplify programming, financing, monitoring. The EU wants to enlarge the instruments of rural development with a four axis model.